AFP shields hepatocellular carcinoma from macrophage phagocytosis by regulating HuR-mediated CD47 translocation in cellular membrane - Yinglian Pan; Qiushi Yin; Zhaoliang Wang; Gang Wu; Kun Liu; Xiaowei Li; Jinchen Liu; Jiangzheng Zeng; Bo Lin; Wei Li; Mingyue Zhu; Mengsen Li (Translational Oncology)
Objectives: Alpha fetoprotein(AFP) overexpression connecting with macrophage dysfunction remain poorly defined. In this study, explore AFP regulates macrophage immunomodulation in hepatocellular carcinoma(HCC) through comprehensive in vitro and in vivo studies. Methods: Immunohistochemical and immunofluorescence staining was used to analyze the relativity of AFP and cellular membrane CD47 expression in clinical 30 HCC tissues, and the expression of AFP and CD47 in HCC cells. The intelligent living-cell high-throughput imaging analyzer was applied to dynamically track and image of macrophages to phagocytize HCC cells. The effect of AFP on regulating the level of CD47 in cellular membrane and growth of tumor in vivo was performed by animal experiment. The association of AFP and CD47 in HCC cells was detected by single cell analysis. Results: The present results indicated that AFP upregulated the localization of CD47 on the HCC cell surface. CD47 overexpression stimulates HCC to escape immune surveillance by transmitting “don't eat me” signals to macrophages, lead to inhibit macrophage to phagocytize HCC cells. Mechanistically, the results demonstrated that AFP enhanced CD47 membrane translocation by interacting with Hu-Antigen R(HuR), an RNA-binding protein that regulates mRNA stability and translation. AFP alters the subcellular distribution of HuR, increasing its cytoplasmic accumulation and binding to CD47 transcript. Conclusions: AFP enhanced CD47 membrane translocation by interacting with HuR. These findings proved that AFP could inhibit macrophage to phagocytize HCC cells by upregulating the localization of CD47 on the HCC cell surface. Combination of AFP with CD47 blockade may be a potential therapeutic strategy for HCC treatment.